(untitled) (Development Service Industry Management, 2024)
The article examines the role and significance of the creative economy in the formation of strategic business development. It is noted that the main result of the strategic development of business structures and economic systems as a whole is the generation of fundamentally new ideas, which are subsequently commercialized in the form of innovations. Innovations and their creative application are becoming the most valuable resources, and creativity is turning into the main source of economic value in the modern world. The circumstances of the emergence of the creative economy and its main features are considered. The concept of creative economy is analyzed. Its features as a systemic phenomenon are revealed. The main components of the creative economy are highlighted. Attention is paid to the important role of business ecosystems in stimulating the creative economy as a new trend in business development. The main stakeholders of the creative economy are considered and their characteristics are given. The influence of the creative economy on rapid overgrowth and socio-economic development in the developed countries of the world and its prospects in Ukraine in the process of post-war recovery are analyzed. The experience of the world’s leading countries in building an innovative and creative economy, despite limited resources and difficult geopolitical conditions, is considered. Considerable attention is paid to the development of the innovation industry with the help of the creative sector of the economy as a key. The formation of new trends in the labor market and their impact on human capital is considered. Attention is paid to issues of strengthening digitalization and development of digital technologies, which leads to the emergence of new directions and ways of promoting creative industries. Key trends in the development of the creative economy and their impact on business development have been formed. The areas of influence of the creative economy on the strategic development of business are systematized.